PENGUATAN PERAN GURU SEBAGAI PEMIMPIN PEMBELAJARAN DI ERA DIGITALISASI DI SMA NEGERI 7 SAPARUA KECAMATAN MALUKU TENGAH - Serpara, Henderika; Wenno, Eldaa Crystle; Camerling, Bella Claudia Frederika (Universitas Pattimura, 2025)
The digital era has transformed the role of teachers from mere information transmitters to facilitators and learning leaders who integrate technology innovatively. This article discusses the results of a Community Service Program (PKM) aimed at enhancing teachers' digital competencies at SMA Negeri 7 Saparua, Central Maluku Regency. The program involved 40 teachers and was conducted in three main stages: preparation, implementation, and reflection and evaluation. The training focused on improving digital literacy, understanding teachers' roles as learning leaders in the digital era, and strengthening professional collaboration. Evaluations revealed that 95% of participants were highly satisfied with the delivery of materials and the use of technology in learning. The program proved effective in enhancing teachers' skills in integrating technology into the teaching process. These findings highlight the importance of continuous training to ensure teachers' adaptability to technological advancements in education.